2022
DOI: 10.1007/s11259-022-10027-4
|View full text |Cite
|
Sign up to set email alerts
|

First genetic detection and characterization of canine parvovirus type 2 (Carnivore protoparvovirus 1) in southwestern Ethiopia

Abstract: The species Carnivore protoparvovirus 1 includes viruses, e.g. canine parvovirus (CPV-2) and feline panleukopenia virus (FPV), which are among the most relevant for pets, causing extremely severe clinical signs and high fatality rate in dogs and cats. Moreover, a broad range of wild hosts, including endangered ones, were proven to be susceptible. Currently, no data on CPV-2 molecular epidemiology and strain characterization are available in Ethiopia, also considering the frequent contacts between domestic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Epidemiological links mediated by both human and animal movement between Asia and Europe have been proven for several companion animal infections, including CPV-2 [ 28 , 60 , 61 , 62 , 63 ]. Similarly, the rising political, economic, and cultural interactions occurring between Asian (especially China) and African countries might have favored the introduction of this lineage, as previously suggested [ 48 , 55 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Epidemiological links mediated by both human and animal movement between Asia and Europe have been proven for several companion animal infections, including CPV-2 [ 28 , 60 , 61 , 62 , 63 ]. Similarly, the rising political, economic, and cultural interactions occurring between Asian (especially China) and African countries might have favored the introduction of this lineage, as previously suggested [ 48 , 55 ].…”
Section: Discussionmentioning
confidence: 89%
“…This finding confirms the huge spreading potential that has characterized the history of CPV-2 and, thus, the need for more effective and systematic monitoring activities to promptly detect and effectively react to emerging viruses. In fact, the increase in population size also mirrored the viral introduction to new areas of the world, and strains belonging to this lineage have been reported particularly in Asia [ 30 , 51 , 52 ], Europe [ 25 , 27 , 29 , 53 ], and Africa [ 31 , 54 , 55 ], although there is also a report from North America [ 12 ]. Furthermore, in recent years, an increasing number of studies from Asia have highlighted not only the progressive spread of the Asian CPV-2c lineage but also the progressive replacement of the circulating CPV-2 strains by this lineage, as if it had potentially greater viral fitness [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, a new CPV-2c variant, also defined as “Asian” or “of Asian origin” started to rapidly spread within Asian countries [ 53 ]. In subsequent years, this Asian lineage has been detected also in non-Asian countries, such as Italy [ 14 ] and other European countries [ 50 , 54 ], Africa [ 24 , [55] , [56] , [57] ], and North America [ 58 ]. As observed in this study, since 2020, a rapid trend of transition from CPV-2a/CPV-2b to CPV-2c predominance was documented also in different Asian countries [ [59] , [60] , [61] , [62] , [63] ].…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic tree showed that the CPV-2b strain (KES-5) clustered with Egyptian, Thai, Nigerian, South Korean, Chinese, Vietnamese, and Indian CPV-2b strains, which agrees with those of Zaher et al [ 18 ] and Elbaz et al [ 20 ]. Tegegne et al [ 46 ] reported that the findings of this strong antigenic similarity between the genotypes of Egyptian and Southeastern Asian countries may be attributed to the strong economic relationship between these countries, with several Chinese business people traveling between these geographic regions, sometimes with their pets.…”
Section: Discussionmentioning
confidence: 99%